A TOXICIDADE DOS MATERIAIS DE CONSTRUÇÃO: UMA BREVE REVISÃO - Gobbi, Mirna; Santos, Mauro; Rola, Sylvia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
While the constructions of the past were made of natural materials, the actual constructions may contain numerous combinations of chemicals and heavy metals. These substances are released in large quantities in buildings, contaminating air and water. The inner environment of buildings, places where people spend most of our daily time, must be free of harmful and intoxicating compounds. When thinking about the toxicity of the material, the harmfulness should be analyzed for both the people and the environment. A material can be toxic in different phases: in the extraction, production, use and disposal, that is, throughout its life cycle, but it is a factor commonly disregarded by the designers. The aim of the paper is to present which topics related to the toxicity of building materials have been published in journals of the Science Direct database in the last 5 years (2012-2017).